2011
DOI: 10.4314/ijbcs.v5i1.68118
|View full text |Cite
|
Sign up to set email alerts
|

Production of bacterial amylase by <i>Bacillus</i> species isolated from rice husk dumpsites in Sokoto metropolis, Nigeria

Abstract: Ten grams (10 g) of soil sample was obtained from a rice husk dumpsite in Sokoto metropolis and analyzed. The species isolated were Bacillus licheniformis, Bacillus lentus and Bacillus megaterium. The Bacillus species isolated were screened for amylolytic activities. The isolate with the widest zone of clearance (A 1 ) was selected for further analysis. The highest activity was observed in B. licheniformis (2.00±0.01 mm) followed by B. lentus (1.96±0.40 mm) and B. megaterium (1.70±0.18 mm) had the least activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Among the microflora, Bacillus genus plays an increasingly important role in food and industrial beverage (Grass et al, 2004). Different species of Bacillus can produce several important enzymes such as amylase, cellulase, tannase, pectinase and betaglucosidase (Schallmey et al, 2004;Oyeleke et al, 2011 Sequencing and phylogenetic analysis PCR products were purified and quantified by electrophoresis in 08% (w/v) agarose gel. The 16S rDNA obtained was sent to the sequencing platform of Cochin Eurofins MW operon (France).…”
Section: Introductionmentioning
confidence: 99%
“…Among the microflora, Bacillus genus plays an increasingly important role in food and industrial beverage (Grass et al, 2004). Different species of Bacillus can produce several important enzymes such as amylase, cellulase, tannase, pectinase and betaglucosidase (Schallmey et al, 2004;Oyeleke et al, 2011 Sequencing and phylogenetic analysis PCR products were purified and quantified by electrophoresis in 08% (w/v) agarose gel. The 16S rDNA obtained was sent to the sequencing platform of Cochin Eurofins MW operon (France).…”
Section: Introductionmentioning
confidence: 99%
“…Both isolates were found to be Gram Positive rod shaped spore forming bacteria. The results of biochemical characteristics of both isolates were compared with results obtained by Oyeleke et al, (2011) and Umayaparvathi et al, (2013) through which the author confirmed the bacterial identity as a Bacillus lichniformis and Bacillus cereus. Similar to our results, Narayanan et al, (2020) also identified B. cereus NDRMN001 from polluted lake soil samples which has the potential to yield 33.19 gm/ L of PHB with fine quality and quantity in a short duration by utilizing cheap nutritional factors.…”
Section: Identification Of Prominent Phb Producing Isolatesmentioning
confidence: 68%
“…The solution was filtered using a cheesecloth and the filtrate was centrifuged at 2000 rpm for 5 min. The decanted supernatant was used as the crude enzyme extract [17,18].…”
Section: Enzyme Extractionmentioning
confidence: 99%